2023
DOI: 10.1002/anie.202316875
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung Isomerization in Radical Copolymerization of Benzyl Vinyl Ether with Pentafluorophenylacrylate Leading to Degradable AAB Periodic Copolymers

Keita Kuroda,
Makoto Ouchi

Abstract: This study revealed benzyl vinyl ether (BnVE) shows the peculiar isomerization propagation in radical copolymerization with an electron‐deficient acrylate carrying pentafluorophenyl group (PFA).  The comonomer pair inherently exhibits the cross‐over propagation feature due to the large difference in electron density.  However, the radical species of PFA was found to undergo a backward isomerization to the penultimate BnVE pendant giving benzyl radical species prior to the propagation with BnVE.  The isomerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Considering the above, a terpolymer made from O2 / O3 / O4 could consist of a random sequence pattern. To clarify in detail, similar to the known radical copolymerization parameters r 1 and r 2 , a certain parameter was tried to be calculated by observing the composition of the polymers at low conversions of copolymerization with varying feed ratios . Unfortunately, this approach was not successful because of the following two reasons; (1) without the catalyst, the polymerization did not proceed at all under diluted conditions (0.10 M) for NMR analysis; (2) when the catalyst was added, the polymerization proceeded very fast at room temperature, which made it difficult to determine the accurate conversion of the monomers at a low conversion (within a second, the conversion change reached a non-negligible level).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the above, a terpolymer made from O2 / O3 / O4 could consist of a random sequence pattern. To clarify in detail, similar to the known radical copolymerization parameters r 1 and r 2 , a certain parameter was tried to be calculated by observing the composition of the polymers at low conversions of copolymerization with varying feed ratios . Unfortunately, this approach was not successful because of the following two reasons; (1) without the catalyst, the polymerization did not proceed at all under diluted conditions (0.10 M) for NMR analysis; (2) when the catalyst was added, the polymerization proceeded very fast at room temperature, which made it difficult to determine the accurate conversion of the monomers at a low conversion (within a second, the conversion change reached a non-negligible level).…”
Section: Resultsmentioning
confidence: 99%
“…Controlling the primary polymer structure has been one of the most fundamental challenges in polymer synthesis because the primary structure sets most of the polymer properties. To construct a well-defined polymer backbone structure, various approaches have been reported so far, e.g., via single monomer addition, specific catalyst preparation to control the repeating unit sequence, or using the intramolecular transformation reaction after one repeating unit addition. Thanks to these efforts, a wide range of newly defined polymer structures have become accessible within the past decade, but major progress has only been made in chain polymerization systems such as vinyl polymer synthesis. Compared with the defined polymer synthesis on chain polymerization, sequence control on step polymerization has not progressed so far, probably because of the difficulty of controlling the latter. Meanwhile, one of the most produced polymers in industries is polyurethane, which is typically prepared by step polymerization using a diol and a diisocyanate as monomers (Figure A). Since the polymerization based on such AA plus BB-type monomers provides always a simple repeating pattern consisting of AA-BB repeating units, the idea of sequence does not make much sense. To implement a more sophisticated polyurethane backbone design, multiple approaches have been reported, such as ring-opening polymerization (ROP) of cyclic monomers or one-by-one monomer addition to synthesize oligomer species. However, those methods often face inevitable limitations on their versatility caused by the taxing synthetic process, and highly defined structures have been achieved only for oligomers, not polymers.…”
Section: Introductionmentioning
confidence: 99%
“…23−25 Recently, Ouchi demonstrated the umpolung isomerization using benzyl vinyl ether in radical copolymerization with pentafluorophenyl acrylate. 26 In addition, Kamigaito also disclosed a radical isomerization polymerization based on 1,5-radical migration reactions. 27 Inspired by Zhu's report about the generation of carbonyl radicals via 1,5-HAT (Scheme 1a), 16 we designed a monomer with a silane linker between the vinyl and benzyl part.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the aforementioned examples, radical polymerization with designed monomers that encourage the propagating radical to transfer to the side chain via 1,5-HAT is less explored. In 1988, Sato et al reported the radical polymerization of vinyl ethers involving 1,5-HAT to embed ethers into the polymer chain (Scheme c). Recently, Ouchi demonstrated the umpolung isomerization using benzyl vinyl ether in radical copolymerization with pentafluorophenyl acrylate . In addition, Kamigaito also disclosed a radical isomerization polymerization based on 1,5-radical migration reactions .…”
Section: Introductionmentioning
confidence: 99%